Virtual reality for emergency medicine training on traffic accident injury treatment: a randomized controlled trial - Li, Zhe; Wang, Wei; Huang, Zheng-Zhuang (Frontiers in Virtual Reality, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of a virtual reality (VR)-based training program in improving emergency physicians’ ability to manage multi-casualty traffic injuries, compared to conventional training methods.MethodsA randomized controlled trial was conducted with 76 emergency physicians from a single hospital. Participants were randomly assigned to either the VR group (n = 38) or the control group (n = 38). The VR group underwent immersive training using a VR simulation of multi-casualty traffic accidents, while the control group received traditional lectures and mannequin-based simulations. Primary outcomes included on-site assessment, triage accuracy, and decision-making in transportation, assessed immediately post-training. Secondary outcomes were participant satisfaction and confidence levels.ResultsThe VR group performed significantly better in on-site assessments (P < 0.05), triage accuracy (P < 0.05), and transportation decision-making (P < 0.05) compared to the control group. The VR group also reported higher satisfaction and confidence in applying learned skills in real-world situations (P < 0.05).ConclusionVR-based training enhances emergency physicians’ performance in managing multi-casualty traffic accidents, demonstrating its potential as a scalable and effective educational tool for emergency medical training.